2005
DOI: 10.1111/j.1365-3059.2005.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia amylovora populations resistant to oxolinic acid in Israel: prevalence, persistence and fitness

Abstract: Oxolinic acid (OA) has been the only bactericide used against fire blight in pear and quince orchards in Israel since 1998. OA-resistant Erwinia amylovora strains ( Ea-OA R ) were detected in several orchards in two restricted areas in the northern Galilee region during 1999-2001. In the following years, resistant strains could not be detected in some of these locations. Documenting the fate of Ea-OA R strains in commercial orchards at eight sites in northern Israel during 2000/03 revealed that the resistant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Some of the oxolinic acid-resistant isolates of B. glumae also exhibited crossresistance to other quinolones, including ciprofloxacin, a fluoroquinolone important in clinical medicine (18). Just two years after oxolinic acid was introduced for control of fire blight in Israel, oxolinic acid-resistant isolates of E. amylovora were detected in several orchards (21). The rapid emergence of resistance to oxolinic acid diminished interest in the use of this antibiotic for sustainable disease control on plants in other countries.…”
Section: Oxolinic Acidmentioning
confidence: 99%
“…Some of the oxolinic acid-resistant isolates of B. glumae also exhibited crossresistance to other quinolones, including ciprofloxacin, a fluoroquinolone important in clinical medicine (18). Just two years after oxolinic acid was introduced for control of fire blight in Israel, oxolinic acid-resistant isolates of E. amylovora were detected in several orchards (21). The rapid emergence of resistance to oxolinic acid diminished interest in the use of this antibiotic for sustainable disease control on plants in other countries.…”
Section: Oxolinic Acidmentioning
confidence: 99%
“…Kleitman et al (19) reported that OA-resistant E. amylovora strains have lower fitness than wild-type strains under no OA treatment. Here, analysis of bacterial populations in rice spikelets showed that the Ser83Arg recombinants grew less than Pg-10, while the growth abilities of the other OA-resistant recombinants were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OA-resistant E. amylovora strains reportedly have lower fitness than wildtype strains (19). However, the implications of OA resistance in the fitness of the bacteria on their host plants remain unclear.…”
mentioning
confidence: 99%
“…However, populations of OA-resistant E. amylovora fluctuated, with OA-resistant strains becoming undetectable in orchards where they previously occurred. Laboratory analyses of OA-resistant strains suggested that these strains were reduced in fitness compared to OA-sensitive strains [39]. Analysis of OA-resistant strains of Burkholderia glumae also showed that the strains were reduced in fitness, as these strains could not survive in rice paddy fields [40].…”
Section: Resistance To Oxolinic Acid and Kasugamycinmentioning
confidence: 99%